0193 An Exploratory, Descriptive Study Of African American's Experiences Of Insomnia Symptoms And Treatment. (27th April 2018) - Williams, N J; Perlis, M; Castor, C; Barnes, A; Chung, A; Kalinowski, J; Roseus, J; Rogers, A; Jean-Louis, G
Abstract: Introduction: Rarely have African American's experiences of insomnia been described from their own perspective. This study aimed to address this issue using qualitative and quantitative methods. Methods: Seventeen men and women with a score ≥10 on the Insomnia Severity Index (ISI) or prescribed medication, consistent with an insomnia disorder, were recruited from the NYC metropolitan area. Participants completed surveys including demographics, health status, the Dysfunctional Beliefs and Attitudes about Sleep Scale-16 (DBAS-16), the Pittsburgh Sleep Quality Index (PSQI), the Connor Davidson Resilience Scale, the Sleep Disorders Questionnaire, SF-12 Health survey, Perceived Stress Scale, and the Decision Self-Efficacy Scale. Two focus groups were conducted to understand participants' views about symptoms, coping style, and treatment preference. Focus group transcripts were imported into NVivo 11 for coding analysis. Transcripts were coded, and codes were grouped into higher order concepts and then in categories. Similar categories were clustered to form overarching themes. Quantitative data were entered into SPSS. Descriptive statistics were used to summarize relevant study variables. Results: Mean age was 49.4 ± 19.3 years. Two people were prescribed Ambien; 47% rated their health as "poor". The mean scores on key sleep measures were (ISI=17.71; DBAS=5.7; and PSQI=8.3). Key themes from the focus groups were: lack of discussion about symptoms with health professionals; low awareness and poor understanding of available treatment; preference for behavioral therapy versus medication; and use of a wide range of strategies (alcohol, Nyquil) to cope with symptoms. Conclusion: To our knowledge, this is the first qualitative study to understand insomnia symptoms and beliefs about treatment among African Americans. We relied on self-diagnosis, as including only those that meet diagnostic criteria for insomnia, could exclude many individuals. Moreover, some patients were experiencing acute insomnia, which may nonetheless, require treatment. In sum, there is a need to design patient-centered interventions that increase knowledge about treatment and empower patients to make informed decisions that are consistent with their treatment preferences and values. Support (If Any): Dr. Williams was supported by NIH/NHLBI K23HL125939. Dr. Jean-Louis was supported by NIH/NIA K07AG052685.